Perceptions of the Use of Quick Response Code Indonesian Standard (QRIS) for Payment and its Impact on Consumer Behavior - Cakra Wirabuana; Ridwan Marbanie; Dana Indra Sensuse; Deden Sumirat Hidayat; Erisva Hakiki Purwaningsih (Faculty of Computer Science Universitas Indonesia, 2024)
Currently the use of cash payments is starting to change to a simpler payment method to non-cash transactions, it is supported by digital payment technology that is developing very quickly. One of the payment methods that can be used through smartphones is using QR codes as a way of payment. Using a qualitative approach, this study aims to analyze the influence of usability, ease of use, and trust factors on consumer acceptance of QR and its impact on purchasing behavior through a qualitative approach. The results of this study will contribute to the development of digital payments, especially based on the resulting perceptions and their impact on purchasing behavior.